Author Correction: Strong indirect coupling between graphene-based mechanical resonators via a phonon cavity - Gang Luo (Nature Portfolio, 2019)
The original version of this Article contained a number of errors. As a result of this, changes have been made to both the PDF and the HTML versions of the Article. A full list of these changes is available online